Overlap food for fish in the Haditha Dam Reservoir (Qadisiyah) Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
Shehadt 683 fish of different fish present in the tank Haditha Dam during the period of February 1993 and the end Maes 1994 to identify the nutritional content of the digestive tract or the stomach for these fish and their impact on the environment of the tank and found that Fish fine linen and Alhalg animal feeding predators feed on small fish, mainly the fish brown plantnutrition